Comparative Analysis of High-Intensity versus Low-to-Moderate Intensity Statin Therapy in Patients Undergoing Rotational Atherectomy for Calcified Coronary Artery Disease - Sang-Suk Choi; Jin Jung; Sung-Ho Her; Kyunyeon Kim; Youngmin Kim; Kyusup Lee; Ki-Dong Yoo; Keon-Woong Moon; Donggyu Moon; Su-Nam Lee; Won-Young Jang; Ik-Jun Choi; et al. (Life, 2023)
(1) Background: Moderate-intensity statin therapy, when compared to high-intensity statin therapy in Asian populations, has shown no significant difference in cardiovascular prognosis in small studies. The aim of this study was to compare the prognosis of patients based on statin intensity following rotational atherectomy (RA) during high-complexity percutaneous coronary intervention (PCI). (2) Methods: The ROCK registry, a multicenter retrospective study, included patients who had undergone rotational atherectomy (RA) during percutaneous coronary intervention (PCI) at nine tertiary medical centers in South Korea between January 2010 and October 2019. The patients were divided into high-intensity statin (H-statin) and moderate/low-intensity statin (M/L-statin) therapy groups. The primary endpoint includes outcomes (cardiac death, target vessel myocardial infarction (MI), and target vessel revascularization (TVR)) within an 18-month follow-up period. (3) Results: In this registry, a total of 540 patients with 583 lesions were included. We excluded 39 lesions from the analysis due to the absence of statin usage. The H-statin group had 394 lesions and the M/L-statin group had 150 lesions. There were no significant differences in baseline characteristics, procedural adverse events without heart failure history, triglycerides, or medications between the two groups. The procedural success rate showed a significant difference between the two groups. Multivariate analysis did not show a significant association between M/L-statin therapy and an increased risk of the primary endpoint. In propensity score matching analysis, no significant difference was observed in the primary endpoint either. (4) Conclusions: In high-complex RA PCI, moderate/low-intensity statin therapy is not inferior to high-intensity statin therapy in Korea.